2021
DOI: 10.3390/v13091844
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Nucleocapsid, Spike and Neutralizing Antibodies, and Viral Load in Patients with Severe COVID-19 Treated with Convalescent Plasma

Abstract: COVID-19 is an ongoing pandemic with high morbidity and mortality. Despite meticulous research, only dexamethasone has shown consistent mortality reduction. Convalescent plasma (CP) infusion might also develop into a safe and effective treatment modality on the basis of recent studies and meta-analyses; however, little is known regarding the kinetics of antibodies in CP recipients. To evaluate the kinetics, we followed 31 CP recipients longitudinally enrolled at a median of 3 days post symptom onset for change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Additional correlation analysis of clinical parameters and antibody levels revealed that anti-spike IgG levels and neutralizing antibody titers were negatively correlated with viral load at inclusion ( Supplementary Figure 1B ). The connection between viral load and both spike and nucleocapsid antibody levels has been shown previously ( 39 , 40 ). Furthermore, there was negative correlation of neutralizing antibody titers and anti-spike IgG levels to CRP at inclusion ( Supplementary Figure 1C ).…”
Section: Resultssupporting
confidence: 64%
“…Additional correlation analysis of clinical parameters and antibody levels revealed that anti-spike IgG levels and neutralizing antibody titers were negatively correlated with viral load at inclusion ( Supplementary Figure 1B ). The connection between viral load and both spike and nucleocapsid antibody levels has been shown previously ( 39 , 40 ). Furthermore, there was negative correlation of neutralizing antibody titers and anti-spike IgG levels to CRP at inclusion ( Supplementary Figure 1C ).…”
Section: Resultssupporting
confidence: 64%
“…In our 8-month follow-up, we also reported that 76% of the patients still had detectable Neutralizing Antibodies (NAb) (1). Many studies reported short-term follow-up observations of less than 6 months (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), whereas others reported longitudinal observations, typically spanning less than 12 months post symptom onset (1,4,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Some studies reported contraction of anti-COVID humoral responses with a stronger initial decline (1,4,(23)(24)(25)27).…”
Section: Introductionmentioning
confidence: 64%
“…An important aspect of monitoring humoral responses has been having access to plasma from the same patients over 14 months. Most reports were based on cross-sectional analysis spanning less than 6 months (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) or up to 12 months (1,4,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Depending on the patient cohort, several studies reported a stronger initial contraction (1,4,(23)(24)(25)27) of anti-COVID humoral responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional correlation analysis of clinical parameters and antibody levels revealed that anti-spike IgG levels and neutralizing antibody titers were negatively correlated with viral load at inclusion (Supplementary Figure 1B). The connection between viral load and both spike and nucleocapsid antibody levels has been shown previously 37,38 . Furthermore, there was negative correlation of neutralizing antibody titers and anti-spike IgG levels to CRP at inclusion (Supplementary Figure 1C).…”
Section: Study Outline and Clinical Parametersmentioning
confidence: 79%